Values of Meaningful Life in Minang Kabau Cultural Philosophy for Middle School Students - Melva Syahrial; Neviyarni S; Firman (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This article discusses the values of meaningful life in the Minang Kabau cultural philosophy for junior high school students. The research method used is Literature Review or literature review. Library research or literature review (literature review, literature research) is research that examines or critically reviews knowledge, ideas, or findings contained in a body of academic-oriented literature. The result of the discussion is that the meaningfulness of life is an individual's appreciation of finding something valuable or important for the individual. The philosophy in Minang Kabau culture will lead junior high school students to discover the values of meaningful life. The meaning of life describes what an individual wants, seeks and hopes for, resulting in optimistic, happy, gloomy, depressed or pessimistic behavior regarding life.